The Polish policy on disability in the perspective of cruel optimism. About the promises that have not been being fulfilled - Głąb, Zbigniew; Kocejko, Magdalena (Understanding Disability: Issues, Research, Reflections, 2021)
The article presents the application of a theoretical approach which is cruel optimism to analyze the situation of people with disabilities in education and the labor market in Poland. Cruel optimism is understood as a set of unfulfilled promises offered and valued by contemporary consumer society. These promises are an indicator of status, and their very existence is associated with social pressure to strive to achieve them at all costs – also at the price of the degradation of the individual. The proposed analysis examines promises made to persons with disabilities as part of various practices and solutions in the fields of vocational education and employment-related activities, as well as indicates the reasons for their failure. Possibilities of avoiding (or reducing) the effect of cruel optimism in shaping disability policy have also been indicated. The summary contains research postulates and recommendations related to the use of cruel optimism approach in the evaluation of programs addressed to people with disabilities.